Numerical study of electrical characteristics of conjugated polymer light-emitting diodes - Abouelaoualim, D.; Assouag, M.; Elmidaoui, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Conjugated polymers now provide a class of processible, film-forming semiconductors and metals. In this work, the electronic properties of polymer lightemitting diodes devices are numerically studied. Our results show how an insulating buffer layer with suitable thickness decreases the barrier height at the cathode and therefore increases the electron injection. We also discuss the effects from persistent charged traps.